Managements for perioperative anxiety in patients with gastrointestinal cancers - Li, Ying; Du, Juan; Du, Li; Li, Shan; Zhang, Jianping (Frontiers in Psychiatry, 2024)
Gastrointestinal (GI) cancers are the most common malignancies, while surgical intervention remains the sole therapeutic approach offering the possibility of a definite cure for cancer. Perioperative anxiety negatively impacts the recovery of GI cancers. Recently, mounting studies have demonstrated that proper nursing interventions may alleviative perioperative anxious illnesses in patients with GI cancers. We conducted a first comprehensive review to summarize all the current evidence on this topic. After a systematically search in the six common databases, eighteen relevant studies were included for further analysis. The present review highlighted that there is a high prevalence of perioperative anxiety in patients with GI cancers (e.g., colorectal cancer, gastric/stomach cancer, hepatocellular carcinoma, gallbladder cancer, and esophageal cancer), while specific nursing interventions are the reliable methods to reduce postoperative anxiety. These nursing strategies include, but are not limited to, therapeutic listening intervention, implementing perioperative music, predictive nursing, progressive relaxation exercises, psychological interventions in the nursing care, comprehensive nursing, continuous nursing care, video-based nursing education, multidisciplinary cooperative continuous care, accelerated rehabilitation nursing, TCM nursing, evidence-based early warning nursing, target nursing care, and high-quality nursing. Since several limitations existed in the eligible studies as well as in this review, a well-designed multicenter RCT with large sample size is still warranted for the confirmation of nursing intervention for managing perioperative anxiety in patients with GI cancers. Also, future studies should focus on the long-term effects of relevant interventions, specific patient populations, multidisciplinary approaches, technological innovations, and educational programs.